Blood knot : a play in seven scenes - Fugard, Athol, author (New York : Samuel French, 1989)
A dramatic play exploring themes of race, identity, and brotherhood in apartheid-era South Africa.
Keywords: Brothers -- Drama; Apartheid -- Drama; South Africa -- Drama. -- Social conditions